Use of service data to inform pediatric HIV-free survival following prevention of mother-to-child transmission programs in rural Malawi - Mandala Justin; Moyo Tiwonge; Torpey Kwasi; Weaver Mark; Suzuki Chiho; Dirks Rebecca; Hayashi Chika (BMC, 2012)
Abstract Background Recent years have seen rapid and significant progress in science and implementation of programs to prevent mother-to-child transmission of HIV. Programs that support PMTCT routinely monitor service provision but very few have measured their effectiveness. The objective of the study was to use service data to inform HIV-free survival among HIV exposed children that received antiretroviral drugs to prevent mother-to-child transmission (PMTCT) of HIV. The study was conducted in two rural districts in Malawi with support from FHI 360. Methods A descriptive observational study of PMTCT outcomes was conducted between June 2005 and June 2009. The dataset included patient-level data of all pregnant women 1) that tested HIV-positive, 2) that were dispensed with antiretroviral prophylaxis, and 3) whose addresses were available for home visits. The data were matched to each woman's corresponding antenatal clinic data from home visit registers. Results Out of 438 children whose home addresses were available, 33 (8%) were lost to follow-up, 35 (8%) were alive but not tested for HIV by the time home visit was conducted, and 52 (12%) were confirmed deceased. A total of 318 children were alive at the time of the home visit and had an HIV antibody test done at median age 15 months. The resulting estimated 24-month probability of HIV-free survival over all children was 78%. Among children who did not receive nevirapine, the estimated 24-month probability of HIV-free survival was 61%, and among those who did receive NVP syrup the estimate was 82%. Conclusions When mothers and newborns received nevirapine, the estimated 24-month probability of HIV-free survival among children was high at 82% (CI: 54% to 99%). However this conclusion should be interpreted cautiously 1) due to the wide confidence interval; and 2) because the confidence interval range includes 55%, which is the natural HIV-free survival rate in the absence of a PMTCT intervention. This analysis highlighted the need of quality data and well-structured home visits to assess PMTCT effectiveness.